Kontroversi Penanganan Bendera One Piece Oleh Aparat Pemerintah Dalam Perspektif Han - Muhammad Jibran Arief; Zaqia Salsabillah (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2026)
The controversy surrounding the handling of the One Piece flag by government officials has sparked debate about the limits of state authority in regulating citizens' symbolic expression in public spaces. The regulation of the flag, which originates from popular culture, under the pretext of maintaining public order and security is considered to have the potential to limit freedom of expression. This article aims to analyze the handling of the One Piece flag by government officials from the perspective of Administrative Law (HAN). This research uses a normative legal research method with a statutory and conceptual approach. The results of the study indicate that restrictions on symbolic expression can only be justified if they are based on law, have a legitimate purpose, and are implemented proportionally. Thus, the actions of government officials must remain within the framework of human rights protection and the principles of the rule of law.